Assessment of Depression Severity During Coronavirus Disease 2019 Pandemic Among the Palestinian Population: A Growing Concern and an Immediate Consideration - Al Zabadi, Hamzeh; Alhroub, Thair; Yaseen, Noor; Haj-Yahya, Maryam (Frontiers in Psychiatry, 2020)
Background Aggressive quarantine and lockdown measures were implemented as protective public health actions during COVID-19 pandemic. Assessing the psychological effects associated with these measures is an important attempt to inform local policymakers’ in an early stage. Yet, little is known about these effects, specifically depression, among the Palestinians. This study aimed to assess the prevalence and predictors of depression among the Palestinian community during this pandemic. Materials and methods A cross-sectional web-based survey throughout social media (Facebook and Instagram) was carried out using an anonymous online questionnaire. The validated and standardized DASS (depression, anxiety, and stress scale) scale was used to measure depression severity. A snowball technique recruiting the general public living in Palestine was conducted. Data was collected between 6- 16 April 2020 which corresponded to the middle interval of strict massive lockdown in Palestine started 22 March to 5 May 2020. Multinomial logistic regression model was developed to predict depression severity. Results About 2819 respondents filled the questionnaire. Depression prevalence was (57.5%; n=1621). Out of them, 66% had mild/moderate severity and 34% had sever/extremely severe degree. Depression severity was negatively associated with age {mild/moderate degree [OR (95%CI) = 0.98 (0.97-0.99)]} and {severe/extremely severe [OR (95%CI) = 0.96 (0.94-0.97)] compared to normal. Males were significantly less likely to have higher depression compared to females {mild\moderate degree [OR (95%CI) = 0.69 (0.57-0.85)] and {severe/extremely severe [OR (95%CI) = 0.52 (0.40-0.86)]}. However, those who reported having inadequate food supply and fewer monthly incomes were more likely to have a higher degree of depression compared to normal. Singles were significantly more likely to have mild/moderate depression compared to those in relationship [OR (95%CI) = 1.31 (1.05-1.64)]. Conclusions High depression prevalence (57.5%) among the Palestinian community during COVID-19 pandemic is a growing Public Health concern. It is essential to provide psychological counseling and treatment during and after the pandemic for the targeted people at high risk (young age/female gender) who were affected psychologically. Strategic long-term policy to address pandemic ramifications, including depression, by implementing comprehensive interventions taking into account socio-economic disparities, vulnerability and inequities are crucial to emerge from this crisis in Palestine.